Poetics of the story “Pacto de sangre” [“Blood covenant”] by Mario Benedetti: a study for the creation of short stories - Cristancho Ruiz, Mario Hernán (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article aims at analyzing the compositional problematics of the short story “Pacto de sangre” [“Blood covenant”] by Mario Benedetti. The starting point for this study are the secrets revealed in the story. After, the story is analyzed in terms of: beginning, development, ending, human condition, intensity, tension, atmosphere, primary story, secondary story. These elements enable the study of the literary treatment of the principal topic: the abandonment of a grandfather and the love of his grandson. Finally, we present conclusions about the poetics implicit in this story and elements for creative research; as well as a short story written by the author based on this study.